The effect of inspiratory and expiratory respiratory muscle training in rowers - Forbes, S.; Game, A.; Syrotuik, D.; Jones, R.; Bell, G. J. (Research in Sports Medicine, 2011)
This study examined inspiratory and expiratory resistive loading combined with strength and endurance training on pulmonary function and rowing performance. Twenty-one male (n = 9) and female (n = 12) rowers were matched on 2000 m simulated rowing race time and gender and randomly assigned to two groups. The experimental group trained respiratory muscles using a device that provided both an inspiratory and expiratory resistance while the control group used a SHAM device. Respiratory muscle training (RMT) or SHAM was performed 6 d/wk concurrent with strength (3 d/wk) and endurance (3 d/wk) training on alternate days for 10 weeks. Respiratory muscle training (RMT) enhanced maximum inspiratory (PImax) and expiratory (PEmax) strength at rest and during recovery from exercise (P < 0.05). Both groups showed improvements in peak VO2, strength, and 2000 m performance time (P < 0.05). It was concluded that RMT is effective for improving respiratory strength but did not facilitate greater improvements to simulated 2000 m rowing performance.